Bodhráns, lambegs, & musical craftsmanship in Northern Ireland. Issue 2 (4th May 2019) - Harte, Colin
ABSTRACT: From its humble beginnings as a ritual instrument, the bodhrán or Irish frame drum has developed into a globally recognised percussion instrument that is found in diverse contexts. This research is about the sophisticated, technical development of this instrument by the drum maker Seamus O'Kane during the height of the Northern Ireland Troubles. The brilliant organological experiments and innovations of O'Kane, altered the bodhrán's design contributing to a rapid expansion of new performance practices and increased interest in the drum. One of O'Kane's signature innovations was the use of skins from the unionist lambeg drum. O'Kane had to precariously negotiate paramilitary politics and drum making in Northern Ireland in order to produce a superior instrument. This paper explores the complex, intertwined nature of Irish political dissidence in County Derry during the Troubles in relation to far-reaching developments in bodhrán drum making. O'Kane's bodhráns, which he continues to make in his County Derry-based workshop, draw from both Irish republican and unionist drum making traditions. This blending of traditions has enabled him to produce an innovative, tunable drum representative of the shared musical cultures of Northern Ireland within a violent, politically divided milieu.